THE PRINCIPLES OF TEACHING CONTEXTUALIZED GRAMMAR IN ENGLISH - Ruziev Khusniddin Bakhritdinovich (Western European Studies, 2024)
This article deals with the principles of teaching contextualized grammar in English. Contextualized Grammar Instruction are given information
Keywords: communicative grammar; contextualization; language acquisition